Comprehensive Analysis of Established Dyslipidemia-Associated Loci in the Diabetes Prevention Program. (December 2016) - Varga, Tibor V.; Winters, Alexandra H.; Jablonski, Kathleen A.; Horton, Edward S.; Khare-Ranade, Prajakta; Knowler, William C.; Marcovina, Santica M.; Renström, Frida; Watson, Karol E.; Goldberg, Ronald; Florez, José C.; Pollin, Toni I.; et al.
Abstract : Background—: We assessed whether 234 established dyslipidemia-associated loci modify the effects of metformin treatment and lifestyle intervention (versus placebo control) on lipid and lipid subfraction levels in the Diabetes Prevention Program randomized controlled trial. Methods and Results—: We tested gene treatment interactions in relation to baseline-adjusted follow-up blood lipid concentrations (high-density lipoprotein [HDL] and low-density lipoprotein-cholesterol, total cholesterol, and triglycerides) and lipoprotein subfraction particle concentrations and size in 2993 participants with pre–diabetes. Of the previously reported single-nucleotide polymorphism associations, 32.5% replicated at P <0.05 with baseline lipid traits. Trait-specific genetic risk scores were robustly associated (3×10 –4 > P >1.1×10 –16 ) with their respective baseline traits for all but 2 traits. Lifestyle modified the effect of the genetic risk score for large HDL particle numbers, such that each risk allele of the genetic risk scores was associated with lower concentrations of large HDL particles at follow-up in the lifestyle arm (β=−0.11 µmol/L per genetic risk scores risk allele; 95% confidence interval, −0.188 to −0.033; P =5×10 –3 ; P interaction =1×10 –3 for lifestyle versus placebo), but not in the metformin or placebo arms ( P >0.05). In the lifestyle arm, participants with high genetic risk had more favorable or similar trait levels at 1-year compared with participants at lower genetic risk at baseline for 17 of the 20 traits. Conclusions—: Improvements in large HDL particle concentrations conferred by lifestyle may be diminished by genetic factors. Lifestyle intervention, however, was successful in offsetting unfavorable genetic loading for most lipid traits. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique Identifier: NCT00004992. Abstract : Supplemental Digital Content is available in the text.